A Short History of Fusible Metals and Alloys – Towards Room Temperature Liquid Metals. Issue 25 (3rd August 2022) - Handschuh‐Wang, Stephan; Gancarz, Tomasz; Uporov, Sergey; Wang, Tao; Gao, Eryuan; Stadler, Florian J.; Zhou, Xuechang
Abstract: Liquid metals are a class of materials with a millennia‐long history, albeit until 200 years ago, mostly centered on mercury‐based applications. The knowledge of mercury's toxicity and the discovery of it's bioaccumulation and biomagnification in the late 20 th century resulted in phasing out mercury for copious application. Lead‐based, bismuth‐based, and sodium‐based technology has partially replaced mercury, but due to toxicity or reactivity issues, replacements for lead and sodium are sought. The discovery of indium and, especially, gallium has allowed for the third generation of alloys with a melting point close to room temperature. This review gives a comprehensive overview of the technological developments of fusible and liquid metals, i. e., metals and alloys with melting points below ca. 250 °C, from the early days to current research and industrial application. Special emphasis is focused on important steppingstones and recent developments of gallium‐based alloys as well as how they could be used for future applications. Abstract : Research on and application of fusible and liquid metals has a history spanning two millennia. In this review, the steppingstones and major advances enabling transition from simple alloys to highly fusible and room temperature liquid metals are illustrated along with their significance and major industrial and scientific applications.